The Correlation between Levels of Gadget Addiction with Level of Vigilance on Ojek Online Driver - Has, Eka Mishbahatul M; Oktalfianto, Eko; Yasmara, Deni (International Journal of Psychosocial Rehabilitation, 2020)
Accidents that occur involve a lot of motorbikes. Motorcycle vehicles have been turned into alternative public transportation called ojek. Accidents can be prevented by increasing the level of vigilance. Currently, an ojek online driver has emerged which the driver can be ordered through the gadget. Accessing the internet through gadgets frequently and repeatedly by the driver is at risk of addiction to the internet. This study aimed to determine the correlation between the level of gadget addiction and the level of vigilance in ojek online drivers in the Surabaya. This study used a correlational design with a cross-sectional study approach and applied a consecutive sampling technique which conducted 53 ojek online drivers operating in the Surabaya. The independent variable was the gadget addiction level and the dependent variable was the level of vigilance. Questioner Young’s Internet Addiction Test (YIAT) was used to measure the level of addiction and the application of PVP-Touch was to measure the level of alertness. Data were analysed using the Spearman rho test (α <0.05). The level of gadget addiction in ojek online drivers was no addiction (51%). The level of vigilance on the ojek online drivers was high vigilance (52.8 %). There was a strong and positive correlation between the level of gadget addiction and the level of alertness (p=0.000). The higher level of addiction generated a lower level of vigilance. Therefore, nurses need to promote the results of this study to ojek online drivers to reduce the number of accidents. Further research needs to be done on the analysis of the factors causing gadget addiction.